Uniportal transcervical video-assisted thoracoscopic surgery (VATS) approach for pulmonary lobectomy combined with transcervical extended mediastinal lymphadenectomy (TEMLA) - Zieliński, Marcin; Rybak, Mariusz; Solarczyk-Bombik, Katarzyna; Wilkojc, Michal; Czajkowski, Wojciech; Kosinski, Sylweriusz; Fryzlewicz, Edward; Nabialek, Tomasz; Pankowski, Juliusz (Journal of Thoracic Disease, 2017)
Background: To present the technique of uniportal transcervical video-assisted thoracoscopic surgery (VATS) approach for pulmonary lobectomy combined with transcervical extended mediastinal lymphadenectomy (TEMLA). Methods: Transcervical extended approach utilizes a typical a 5–8 centimeters collar incision in the neck. The critical technical point enabling a wide access to the chest is an elevation of the sternal manubrium with a special retractor (modified Rochard frame, Asculap-Chifa Company). A bilateral visualization of the laryngeal recurrent and vagus nerves is usually performed to avoid injury of these structures. The uniportal transcervical VATS lobectomy for NSCLC is preceded by TEMLA to enable optimal intraoperative staging of the mediastinal nodes and perform extensive bilateral lymphadenectomy, which theoretically might affect survival. VATS lobectomy is the next step after obtaining results of intraoperative examination of the nodes. Ventilation of the operated lung is disconnected and the mediastinal pleura is opened. Pleural adhesions are divided. The branches of the pulmonary artery and vein and the lobar bronchus are sequentially dissected and managed with endo staplers. The fissure is divided with endo stapler and the resected lobe is removed in endobag. Results: There were 9 patients operated on in the period 1.2.2016–30.7.2016. In one patient with left lower lobe tumor we had to convert to uniportal VATS left lower lobectomy due to extensive adhesions. There was no mortality and complications occurred in 2 patients. The mean operative time was 258.1 min (200–385 min) for the whole TEMLA procedure with imprint cytology and lobectomy and 168.1 min (110–295 min) for a lobectomy solely. Conclusions: A uniportal transcervical video-assisted thoracoscopic surgery (VATS) approach for pulmonary lobectomy combined with TEMLA provides an opportunity for radical pulmonary resection and super radical extensive mediastinal lymphadenectomy.